ANALISIS PENGGUNAAN BAHASA JURNALISTIK DALAM BERITA DI MEDIA DARING BATAMNEWS - Lasmaria Sinaga, Juwita; Malik, Abdul; Lolita, Asri; Wahyusari, Ahada; Suhardi; Elfitra, Legi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the analysis of journalistic language use in the online media Batamnews. The research data source comes from news published in the June edition of Batamnews. The data studied are words and sentences contained in the news. Data collection techniques used include documentation and hermeneutics. The data analysis technique applied is content analysis, which is carried out through the stages of reading, analyzing, describing, and concluding the forms of journalistic language use in the online media Batamnews. This study aims to describe how journalistic language is used in the media. The method used is a qualitative descriptive method, in which the researcher acts as the main instrument, assisted by a data analysis guideline table. The results show that there are 21 news items in the June edition that do not fully comply with journalistic language rules. This nonconformity is found in the aspect of the use of short and concise language, straightforward, clear, and populist.